2009
DOI: 10.1016/j.biortech.2009.03.077
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of cheese whey wastewater by sequential anaerobic and aerobic steps in a single digester at pilot scale

Abstract: The treatment of cheese whey wastewater by sequential anaerobic and aerobic steps in a single digester at pilot scale Frigon, J.-C.; Breton, J.; Bruneau, T.; Moletta, R.; Guiot, S. R. The treatment of reconstituted whey wastewater was performed in a 400 L digester at 20°C, with an anaerobic digestion step, followed by a step of aerobic treatment at low oxygen concentration in the same digester. In a first set of 48 cycles, total cycle time (T C ) of 2, 3 and 4 days were tested at varying organic loading rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 24 publications
1
25
0
6
Order By: Relevance
“…It is observed that Frigon et al [83] achieved the highest COD removal at the shortest HRT and at psychrophilic conditions (20 °C), in a single digester of anaerobic and aerobic treatment. Therefore the use of integrated reactors (anaerobic/aerobic digestion) with stacked configuration in treating high strength industrial wastewaters is advantageous in terms of minimal space requirements, low capital cost and COD removal efficiencies obtained.…”
Section: Anaerobic/aerobic Reactorsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is observed that Frigon et al [83] achieved the highest COD removal at the shortest HRT and at psychrophilic conditions (20 °C), in a single digester of anaerobic and aerobic treatment. Therefore the use of integrated reactors (anaerobic/aerobic digestion) with stacked configuration in treating high strength industrial wastewaters is advantageous in terms of minimal space requirements, low capital cost and COD removal efficiencies obtained.…”
Section: Anaerobic/aerobic Reactorsmentioning
confidence: 99%
“…The anaerobic degradation of the main fraction of organic matter and then the aerobic treatment of the partially treated wastewaters, in order to reduce the final organic load of the effluent and to fulfill the discharge requirements [83]. The aerobic treatment step can be provided by aerated ponds [98,117], or aerobic jet loop membrane reactors [3].…”
Section: Anaerobic/aerobic Reactorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with specifi c biomass activity, trophic differentiation can be seen in the system: methanogens predominantly live at the bott om of the bulk liquid, while acidogens inhabit suspended fl ocs. When the soluble O 2 rose to 0.5 mg/L during the aerobic phase, the COD was reduced to (88±3) % in a 2-day total cycle time at 1.55 kg/ (m 3 ·day) (111).…”
Section: Biological Treatmentmentioning
confidence: 99%
“…It shows high biodegradability and relatively high alkalinity. Cheese whey accounts for 70% to 75% of the lactose present in the milk and 10% to 15% of soluble proteins, what results in chemical oxygen demand (COD) between 50 and 70 g L -1 (Frigon et al, 2009). …”
Section: Cheese Whey Characterizationmentioning
confidence: 99%